KEMAMPUAN BERPIKIR KREATIF SISWA MELALUI CREATIVE PROBLEM SOLVING - Windi Hadianti Tarlina; Ekasatya Aldila Afriansyah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2016)
Creative thinking ability is the one of important things in mathematics lesson. In developing such creative thinking ability, teachers must be good at giving ideas and issues which are relatively different from before, so that we can find something new. The authors formulate the problem: Do the creative thinking abilities of students who received Creative Problem Solving learning better than students who received conventional learning?Quasi-experimental research with experimental design (Nonequivalent group pretest-posttest design) aims to determine students' achievement of creative thinking abilities through Creative Problem Solving. The benefits of this research are expected to improve the students' creative thinking ability through CPS further in SMPN 2 South Tarogong. The instrument used in this study is a written test form with a description of the subject lines and angles. The population was all students of class VIII SMPN 2 South Tarogong; the sample of the selected class is VII-D and VII-E class. From the analysis of data normality test results of initial tests, obtained a score in the experimental class was not normal, so the test followed by Mann Whitney test, the gain was normalized. These results indicate that: (1) The improvement of students’ creative thinking ability who received Creative Problem Solving learning better than students who received conventional learning, (2) The improvement of students’ creative thinking ability who received Creative Problem Solving learning included into the high category, (3) The students’ attitude of the experiment class on the subjects of mathematics and Creative Problem Solving learning was dominated by a positive attitude. Keywords: Creative thinking ability, Creative Problem Solving, conventional, experimental methods.